Tác động của giá dầu, tỷ giá, lạm phát lên tăng trưởng kinh tế ở Việt Nam - Ngô Thái , Hưng; Nguyễn Thị Cẩm , Tú; Bùi Minh , Bảo; Hồ Linh , Đan; Nguyễn Thanh , Hiền (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
This study contributes to the related literature by looking into the impact of oil prices, inflation, and exchange rates on economic growth in Vietnam using data spanning from 1995 to 2020 on quarter basis. By utilizing the quantile regression including the novel quantile on quantile regression (QQR) developed by Sim and Zhou (2015) and non-parametric Granger causality in quantiles techniques proposed by Troster et al. (2018), the authors evaluate the ways in which the quantiles of the independent variables impact the quantiles of economic growth. The findings from the QQR suggest that oil prices, inflation, and exchange rates significantly impact economic growth in all quantiles. More importantly, the results from the Granger causality test highlight that there exists a bidirectional relationship between the examined indicators at different quantiles. The consistency of the results demonstrates that the findings are reliable and appropriate for supporting strategies aimed at increasing economic growth in Vietnam. The policy implications for Vietnam are also discussed.